Current Progress in Evolutionary Comparative Genomics of Great Apes - Yousaf, Aisha; Liu, Junfeng; Ye, Sicheng; Chen, Hua (Frontiers in Genetics, 2021)
The availability of high quality genome sequences of great ape species provides unprecedented opportunities for genomic analysis. Herein, we reviewed the recent progress in evolutionary comparative genomic studies of the existing great ape species, including human, chimpanzee, bonobo, gorilla, and orangutan. We elaborate discovery on evolutionary history, natural selection, structural variations and new genes of these species, which is informative for understanding the origin of human-specific phenotypes.